Correlation between Sanitation of Cow Stalls on Flies Density and Cryptosporidium sp. Manifestations - Drajad, Rahadinda Mutia Dhamar; Nurdian, Yudha; Astuti, Ida Srisurani Wiji; Utami, Wiwien Sugih; Armiyanti, Yunita; Hermansyah, Bagus (Jurnal Medik Veteriner, 2023)
The purpose of this study was to determine the correlation of stall sanitation on fly density and Cryptosporidium sp. presence on housefly. This study type was observational with a cross sectional approach in Jatian Village, Pakusari District, Jember Regency on December 2021 - February 2022. Data type was primary data that obtained using interview and observation. The correlation test that used was contingency coefficient test. The results showed that 77,5% of the stall had high fly density. Prevalence of Cryptosporidium sp. on housefly was 10%. Statistical analysis showed that cattle manure handling affected fly density (pâ‰¤0,05) with low correlation (r=0,384), meanwhile air vents affected Cryptosporidium sp. presence on housefly (pâ‰¤0,05) with low correlation (r=0,359). Farmers were suggested to keep the stall sanitation optimal to prevent Cryptosporidium transmission to humans.